the ADOLESCENT REPRODUCTIVE HEALTH COUNSELING PROVIDED TO PREVENT STUNTING IN MERI MOJOKERTO: THE ADOLESCENT REPRODUCTIVE HEALTH COUNSELING PROVIDED TO PREVENT STUNTING IN MERI MOJOKERTO - nurul agustin (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2024)
Stunting is a growth and development disorder experienced by children, as due to lack of nutritional intake for a long time. Community service aims to reduce stunting rates in Meri, Kranggan District, Mojokerto City. Problems identified include knowledge about stunting. The solution offered is by providing counseling about reproductive health to teenagers to provide knowledge about preventing stunting to their families, with steps to increase knowledge that can be carried out through health education about reproductive health and stunting. This health education can be given to a family as the smallest unit of society. With this health education, it will increase family knowledge and attitudes about stunting, and active participation of teenagers. The output target to be achieved is increasing insight regarding adolescent reproductive health and stunting. The implementation method is by providing counseling to young MA Permata students. This program is expected to have a significant positive impact in Meri.